5 - Construction de la paix par les compétences de vie courante en milieux scolaires de Bukavu/RDC. Regard sur les approches « Peace-campings et Clubs de paix scolaires » - Dieumerci Aksanti Cirhibuka (African Sociological Review, 2022)
This study focuses on “School Clubs and Peace-camp-sites”, which are the extra-curricular educational activities organized by schools in partnership with nongovernmental organizations with the ultimate objective of cultivating peace among young pupils. It shows how they can contribute to the construction of lasting peace making it possible to promote knowledge, competences, attitudes and values necessary to bring changes in their behaviour.